Design and Analysis of a Two-Stage Cascade System for Heating and Hot Water Production in Nearly Zero-Energy Buildings Using Thermoelectric Technology - Javier Ordóñez; Sergio Díaz de Garayo; Álvaro Martínez; Fernando Algarra; David Astrain (Buildings)
This paper proposes an innovative system that integrates two thermoelectric heat pumps (one air–water and the other water–water) with two thermal storage tanks at different temperatures to provide heating and domestic hot water to a 73.3 m2 passive-house-certified dwelling in Pamplona (Spain). The air–water thermoelectric heat pump extracts heat from the ambient air and provides heat to a tank at intermediate temperature, which supplies water to a radiant floor. The water–water heat pump takes heat from this tank and provides heat to the other tank, at higher temperature, which supplies domestic hot water. The system performance and comfort conditions are computationally analyzed during the month of January under the climate of Pamplona and under different European climates. The COP of the system lays between 1.3 and 1.7, depending on the climate, because of the low COP of the air–water thermoelectric heat pump. However, it is able to provide water for the radiant floor and to maintain the temperature of the dwelling above 20 °C 99.8% of the time. Moreover, it provides domestic hot water at a temperature above 43 °C 99.9% of the time. Noteworthy is the fact that the water–water heat pump presents a COP close to 4, which opens up the possibilities of working in combination with more efficient heat pumps for the first stage.